Pneumococcal hydrogen peroxide regulates host cell kinase activity - Bazant, Jasmin; Weiss, Astrid; Baldauf, Julia; Schermuly, Ralph Theo; Hain, Torsten; Lucas, Rudolf; Mraheil, Mobarak Abu (Frontiers in Immunology, 2024)
Introduction Protein kinases are indispensable reversible molecular switches that adapt and control protein functions during cellular processes requiring rapid responses to internal and external events. Bacterial infections can affect kinase-mediated phosphorylation events, with consequences for both innate and adaptive immunity, through regulation of antigen presentation, pathogen recognition, cell invasiveness and phagocytosis. Streptococcus pneumoniae (Spn), a human respiratory tract pathogen and a major cause of community-acquired pneumoniae, affects phosphorylation-based signalling of several kinases, but the pneumococcal mediator(s) involved in this process remain elusive. In this study, we investigated the influence of pneumococcal H2O2 on the protein kinase activity of the human lung epithelial H441 cell line, a generally accepted model of alveolar epithelial cells. Methods We performed kinome analysis using PamGene microarray chips and protein analysis in Western blotting in H441 lung cells infected with Spn wild type (SpnWT) or with SpnΔlctOΔspxB -a deletion mutant strongly attenuated in H2O2 production- to assess the impact of pneumococcal hydrogen peroxide (H2O2) on global protein kinase activity profiles. Results Our kinome analysis provides direct evidence that kinase activity profiles in infected H441 cells significantly vary according to the levels of pneumococcal H2O2. A large number of kinases in H441 cells infected with SpnWT are significantly downregulated, whereas this no longer occurs in cells infected with the mutant SpnΔlctOΔspxB strain, which lacks H2O2. In particular, we describe for the first time H2O2-mediated downregulation of Protein kinase B (Akt1) and activation of lymphocyte-specific tyrosine protein kinase (Lck) via H2O2-mediated phosphorylation.